Islet Cell Response to High Fat Programming in Neonate, Weanling and Adolescent Wistar Rats - Cerf, Marlon E; Louw, Johan (JOP. Journal of the Pancreas, 2014)
Context High fat programming, by exposure to a high saturated fat diet during fetal and/or lactational life induces metabolic derangements and alters islet cell architecture in neonate and weanling rats. Objective The present study assessed metabolic changes and islet cell dynamics in response to high fat maintenance during specific developmental periods in adolescent rats, with some parameters also studied in neonate and weanling rats. Methods The experimental groups comprised neonates, weanlings and adolescents maintained on a high fat diet during specific periods of fetal, lactational and/or postnatal life. Control neonates, weanlings and adolescents were maintained on a standard laboratory (control or low fat) diet. Fetal high fat programmed (i.e., maintained on a high fat diet exclusively during fetal life) neonates were insulin resistant. Results Weanlings maintained on a high fat diet throughout fetal and lactational life had increased pancreas weights. Fetal high fat programmed adolescents presented a normal phenotype mimicking the control adolescents. Adolescents maintained on a postnatal high fat diet had increased body weights, hyperglycemia, hyperinsulinemia, hyperleptinemia and insulin resistance displaying beta cell hypertrophy and increased islet cell proliferation. Adolescents maintained on a fetal and postnatal high fat diet had increased body weights, hyperleptinemia, hyperinsulinemia and insulin resistance. Conclusions High fat programming induces various diabetogenic phenotypes which present at different life stages. The postnatal period from birth to adolescence represents an extension for high fat programming of metabolic disease. Image: Beta cell volume in adolescent rats